Risk mapping and eco‐anthropogenic assessment of anthrax in the upper Zambezi basin - Harvey K. Kamboyi; Michel deGarine‐Wichatitsky; Mudenda B. Hang'ombe; Musso Munyeme (Veterinary Medicine and Science, 2019)
Abstract In Zambia, anthrax has emerged as a serious disease decimating humans, livestock and wildlife with devastating effects on eco‐tourism resulting in the destabilization of major pristine wildlife sanctuaries. Consequently, the thrust of this study was to establish the spatial distribution of anthrax and determine ecological drivers of its recurrence, maintenance and epidemiological linkage to anthropogenic activities. Environmental and biological samples were collected within the livestock production and conservation areas (n = 80). Each sample was serially tested for Bacillus anthracis positivity through blood agar culture and Gram stain technique, and then confirmation by multiplex polymerase chain reaction (MPCR). Questionnaires (n = 113) were conducted at independently distinct villages in terms of space and time. Most respondents showed that animals that died from anthrax were not properly disposed off. More likely than not, poverty being the main driver for anthrax carcass dressing and meat distribution contributed to environmental contamination with anthrax spores in areas where the animals subsequently died resulting in further environmental contamination, which is the major source of primary infection for livestock and wildlife. From the samples, 15 pure isolates of anthrax were obtained which were spatially distributed across four districts. Twelve, biologically plausible variables were found to be highly significant on multivariable logistic regression analysis model for questionnaires which included herd size (odds = 10.46; P = 0.005; CI 8.8–16), carcass disposal method (odds = 6.9; P = 0.001; CI = 3.4–9.8), access to veterinary services (odds = 10.87; P = 0.004; CI = 4.8–15.9) and management system (odds = 2.57; P = 0.001; CI = 1.3–7.5). In summary, the majority (78.7%) of anthrax outbreaks were observed in areas with low veterinary services (χ2 = 8.6162, P = 0.013) within the newly created districts of Nalolo, Mwandi and Luampa.